A Cognitive Semantic Study of Oxymoron in Nali’s Collection of Poems - Nabaz Ismael Hamad (Zanco Journal of Humanity Sciences)
This paper investigates oxymoron within cognitive semantic theory and attempts to find out how the meaning is conceptually constructed in oxymoron through combining two opposite lexical items, and what mental process activates this meaning construction. The study data is collected from Nali’s Collection of Poems who is one of the greatest Kurdish classic poets in terms of his language craftsmanship. The examples are analysed under Conceptual Blending Theory via Linguistic Introspection Analysis method. The study realises that the uses of oxymoron does imply the co-existing features of both constituting lexical items, but there is an accentuation to one of them depending on various factors like the whole verse or even the whole poem interpretation. The user purposefully profiles a particular construal in each oxymoron. The study concludes that in oxymoron meaning is constructed by a certain type of conceptual blending network that is double-scope network in which both input spaces have the same elements but different frames. Then compression happens to project the input spaces elements to the blended space as well as each input space frame makes central contribution to organize the frame of the blended space. An emergent structure rises in the blended spaces with a new frame, and that is the (new) meaning being constructed.